Fealaan and Foalaan in the Lumaa and shuruh - Qawam, Yathrib Osama; Hamid, Diaa (Al-Adab Journal, 2021)
The multitude of multitudes was distinguished from other multitudes by the abundance of their buildings, reaching twenty-three according to the months, and they were distinguished by actions and actions with actors and dependents from other buildings of the multitude of multitudes that are combined on them from the buildings that refer to the singular. Explanations in detail and representation, and opinions in these buildings varied between gloss and explanations, as well as missing between the explanations themselves, and I chose from them two constructions (verbs and verbs) due to the large number of constructs that combine (two actions) and their participation with (verbs) in (action, action, and action) And a subject), and the eighty-year-old and Ibn Burhan on Ibn Jinni recovered some of these buildings, and he compiled (two verbs) eight constructs (verb, action, action, effective, action, action, action, action) and combined (four acts) Do, perform, doer, doer) - Some of these buildings are expelled by analogy with two actions, and they are not analogous to the other building (two actions), and some of them came on analogy in the builders. The buildings enriched the office Morphology, as well as some opinions that are concerned with the morphological significance of the building.